2018
DOI: 10.1016/j.jpsychores.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Does emotional talk vary with fears of cancer recurrence trajectory? A content analysis of interactions between women with breast cancer and their therapeutic radiographers

Abstract: The emotional content expressed matched features outlined in the Lee-Jones et al. (1997) FCR model, and showed evidence of avoidance in increasing FCR trajectory patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…The formulation of this merger would also reflect FCR's new consensus definition . Other support for the merger of cognition and emotions comes from recent reviews of the model by Lee‐Jones et al by Barracliffe et al The authors provide qualitative and diary support of the model by Lee‐Jones and their findings points to the parallel underplay of cognitions and emotions processed simultaneously when cancer survivors experience FCR. Reflecting on the many other FCR models that have emphasized the intertwined nature of cognition and emotions such as with the metacognition theory approach by Fardell et al, the proposed revised model again highlights this unique evolving empirical finding to FCR models.…”
Section: Discussionmentioning
confidence: 97%
“…The formulation of this merger would also reflect FCR's new consensus definition . Other support for the merger of cognition and emotions comes from recent reviews of the model by Lee‐Jones et al by Barracliffe et al The authors provide qualitative and diary support of the model by Lee‐Jones and their findings points to the parallel underplay of cognitions and emotions processed simultaneously when cancer survivors experience FCR. Reflecting on the many other FCR models that have emphasized the intertwined nature of cognition and emotions such as with the metacognition theory approach by Fardell et al, the proposed revised model again highlights this unique evolving empirical finding to FCR models.…”
Section: Discussionmentioning
confidence: 97%
“…Psychiatric disorder, non-English speaking, metastatic disease or consultant withdrawal were exclusion variables. Detailed sampling has been reported elsewhere [1]. See Appendix 1 for flow chart.…”
Section: Samplementioning
confidence: 99%
“…We have reported on the sequence of emotional cues that patients express and the type of response from Therapeutic Radiographers [16]. In addition, in a mixed-methods study we found that the expression of certain emotional content was linked to the FCR trajectory over radiotherapy treatment using a daily diary record [1]. Our interest was to explore the specific effects of patients raising emotional issues in appointments with their TR during their treatment.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported previously on 12 patients from the FORECAST study that completed daily diary ratings of FCR [18]. Selection of two types of patients was conducted, namely, those (n = 6) patients with a clear positive trajectory, i.e.…”
Section: Introductionmentioning
confidence: 99%